EXPERIMENTAL STUDIES OF HYDRO-PNEUMATIC SEEDING MECHANISM OPERATION - Prasolov, Ye. Ya.; Ryzhkova, T. Yu.; Velychko, K. S. (Scientific Progress & Innovations, 2020)
Well-known constructions of hydraulic and pneumatic seeding mechanisms lead to the injury of seeds and their sprouts during sowing. It is proposed to construct devices for the improvement of seeding quality in a modernized hydro-pneumatic seed drill. Large and sound seeds of cucumber and marrow varieties, which are resistant to drought, were chosen for the research. It includes a system for seed disinfection, a device for seed treatment with ultra-high frequency radiation, a device for counting the number of leaves of a germi-nated crop and counting the number of seeds. The design of openers which provide the uniformity of sowing germinated seeds by a hydro-pneumatic way was modernized. The physical and mechanical properties of vegetable seeds were studied. It has been determined that the coefficient of seeds friction with the working surface of a spoon and the walls of a seed box and other auxiliary elements affects the quality of sowing, the number of omissions and damage to sprouts during sowing. It has been found out that the least friction of seeds with working surfaces is in polyvinylchloride or fluoroplastic materials. Significant reduction of the friction coefficient is observed when using germinated seeds as sowing material, then the improvement of sowing quality of germinated seeds in comparison with non-germinated is on average 48 %. The use of the proposed water-seed solution, which moistens seeds during sowing, improves the quality of gripping seeds with a spoon. This makes it possible to reorient seeds in a spoon and ensure their secure fixation. The optimal parameters of a hydro-pneumatic seed drill have been determined according to three factors. Analysis of the results showed that seed omission was 2.55 % at the determining parameters within: the frequency of shaft rotation – 18.42… 19.17 sec-1, the spring stiffness of a holder – 541… 547 N/m, the air flow rate towards the seed box – 5.78…6.15 m/s. The proposed technology enables to avoid seed omission and damage to sprouts during sowing vegetables by a hydro-pneumatic seeding mechanism, which provides saving as well as obtaining early yield.